Final Dispute Settlement in Numbers: Report of an Examination of Final Dispute Settlement in the Utrecht District Court - Paulien WILLEMSEN; Rick BUSSCHER; Niels GROOT; Philip LANGBROEK; Linnea LANGERAK (Transylvanian Review of Administrative Sciences, 2009)
In the Netherlands the administrative court sometimes has the possibility to settle the case without jeopardizing the separation of administrative and judicial responsibilities based on the separation of powers doctrine. This paper addresses the question of how often administrative courts use the powers they currently have for final settlement of disputes and whether they make optimal use of these powers.